MEDICINAL PLANTS EXTRACTS ANTIMICROBIAL ACTIVITY STUDY AGAINST STAFILOCOCCI SKIN ISOLATES WITH DIFFERENT TYPES OF MLS-RESISTANCE - Юрчишин, О. І. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Pulse, 2019)
242 ethanolic extracts of 183 medicinal and spice-aromatic plants antimicrobial activity study was performed against 2 skin strains of staphylococci with inducible and constitutive mechanisms of MLS-resistance (macrolides, lincosamides and streptogram B) by agar diffusion method. Orthilia secunda L. House (Ramischia secunda L.Garcke) herb, Vaccinium myrtillus L. and Potentilla repens L. aerial part, Geranium pratense L. and Polygonum bistorta L. rhizomes, Cinnamomum aromaticum Nees / Cinnamomun cassia Blume bark, Punica granatum L. fruit pericarp, Thea sinensis L. leaves, Viburnum opulus L. fruits extracts showed remarkable antimicrobial activity (d inhibition zone ≥15 mm) against S. epidermidis with inducible mechanisms of MLS-resistance. Extract of Sambucus ebulus L. leaves, Viburnum opulus L. fruits and Scrophularia nodosa L. aerial part were active against S. aureus strain with constitutive MLS-resistance phenotype. High antimicrobial activity (MBC <200 μg/ml by agar serial dilution method) against 25 skin isolates of staphylococci showed extracts of Geranium pratense L., Geranium palustre L. aerial part and Evernia furfuracea ( L.) Mann. thallus.